Replacement of All Arginine Residues with Canavanine in MazF-bs mRNA Interferase Changes Its Specificity - Ishida, Yojiro (American Society for Biochemistry and Molecular Biology, 2013)
Replacement of a specific amino acid residue in a protein with nonnatural analogues is highly challenging because of their cellular toxicity. We demonstrate for the first time the replacement of all arginine (Arg) residues in a protein with canavanine (Can), a toxic Arg analogue. All Arg residues in the 5-base specific (UACAU) mRNA interferase from Bacillus subtilis (MazF-bs(arg)) were replaced with Can by using the single-protein production system in Escherichia coli. The resulting MazF-bs(can) gained a 6-base recognition sequence, UACAUA, for RNA cleavage instead of the 5-base sequence, UACAU, for MazF-bs(arg). Mass spectrometry analysis confirmed that all Arg residues were replaced with Can. The present system offers a novel approach to create new functional proteins by replacing a specific amino acid in a protein with its analogues.